2015
DOI: 10.1017/s1751731114002559
|View full text |Cite
|
Sign up to set email alerts
|

Preference by sheep for endophyte-infected tall fescue grown adjacent to or at a distance from alfalfa

Abstract: Two experiments were conducted to assess preference by sheep for endophyte-infected tall fescue growing in monoculture at least 5 m away from alfalfa (fescue-middle (FM)) over endophyte-infected tall fescue growing adjacent (0.2 to 1 m; fescue-alfalfa (FA)) to alfalfa (FA), and the effect of legume scent on preference for endophyte-infected tall fescue. In Experiment 1, 10 six-month-old lambs were offered for 12 days a choice of freshly harvested FA and FM. On days 13 and 14, lambs were offered the same choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…Consistent with this hypothesis, EV concentration in E+TF was greater when the plant grew adjacent to Alf or BFT than when it grew in a monoculture. These results are consistent with findings from a previous study where E+TF had greater EV concentrations when growing adjacent to Alf than when growing in monoculture (Friend, Provenza, & Villalba, ). Interestingly, Friend et al.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this hypothesis, EV concentration in E+TF was greater when the plant grew adjacent to Alf or BFT than when it grew in a monoculture. These results are consistent with findings from a previous study where E+TF had greater EV concentrations when growing adjacent to Alf than when growing in monoculture (Friend, Provenza, & Villalba, ). Interestingly, Friend et al.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, Friend et al. () also found that when sheep were given a choice between E+TF growing adjacent to Alf or in monoculture (with less EV), sheep preferred E+TF with greater EV which also had more crude protein, but only during the first hour of the feeding period. The correlation coefficient between EV and N in E+TF indicated a significant positive relationship which may imply that increased N renders greater EV in E+TF.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this short grazing scheme enabled us to detect which cultivar cattle grazed first, indicating the favorite cultivar. During the first hour of grazing, sheep preferred to graze a tall fescue and alfalfa mixture with higher CP, even though alkaloid content was higher, vs. tall fescue with alfalfa grown 5 m away with a lower CP and alkaloid content; preference for the high-alkaloid mixture decreased after the first hour (Friend et al, 2015). In grazing studies, cattle (Lyman et al, 2012) and sheep (Friend et al, 2015) were observed to adjust their intake of CTE+ tall fescue over successive grazing bouts within each day in an attempt to balance intake of alkaloids.…”
Section: Grazing Similarities Between Toxic and Nontoxic Cultivarsmentioning
confidence: 98%
“…These studies used 21- (Jackson et al, 1984) and 53-d feeding trials. In grazing studies, cattle (Lyman et al, 2012) and sheep (Friend et al, 2015) were observed to adjust their intake of CTE+ tall fescue over successive grazing bouts within each day in an attempt to balance intake of alkaloids. Additionally, this short grazing scheme enabled us to detect which cultivar cattle grazed first, indicating the favorite cultivar.…”
Section: Grazing Similarities Between Toxic and Nontoxic Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation